Exploring senior doctors' beliefs and attitudes regarding mental illness within the medical profession: a qualitative study. Issue 9 (16th September 2016) - Bianchi, Eleonora F; Bhattacharyya, Mimi R; Meakin, Richard
Abstract : Objective: To explore the views of senior doctors on mental illness within the medical profession. Background: There has been increasing interest on the issue of doctors' mental health. However, there have been few qualitative studies on senior doctors' general attitude towards mental illness within the medical profession. Setting: Large North London teaching hospital. Participants: 13 hospital consultants and senior academic general practitioners. Methods: A qualitative study involving semi-structured interviews and reflective work. The outcome measures were the themes derived from the thematic framework approach to analysis. Results: Four main themes were identified. (1) 'Doctors' attitudes to mental illness'—doctors felt that there remained a significant stigma attached to suffering from a mental illness within the profession. (2) 'Barriers to seeking help'—doctors felt that there were numerous barriers to seeking help such as negative career implications, being perceived as weak, denial and fear of prejudice. (3) 'Support'—doctors felt that the use of support depended on certainty concerning confidentiality, which for occupational health was not thought to be guaranteed. Confiding in colleagues was rare except among close friends. Supervision for all doctors was raised. (4) 'General Medical Council (GMC) involvement'—doctors felt that uneasy referring colleagues to the GMC and the appraisal and revalidation process was thought not to be thorough enough in picking up doctors with a mental illness. Conclusions: Owing to the small size of this study, the conclusions are limited; however, if the findings are confirmed by larger studies, they suggest that greater efforts are needed to destigmatise mental illness in the profession and improve support for doctors. Additional research should be carried out into doctors' views on occupational health services in managing doctors with mental illness, the provision of supervision for all doctors and the effectiveness of the current appraisal and revalidation process at identifying doctors with a mental illness.